2014
DOI: 10.1139/cjz-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

Lack of detectable genetic differentiation between den populations of the Prairie Rattlesnake (Crotalusviridis) in a fragmented landscape

Abstract: Numerous studies have reported genetic fragmentation of species whose habitat has been modified by roads and other anthropogenic features, but it is still not clear how most species respond to roads and whether genetic effects can be detected over a limited number of generations. We used road-crossing models and population genetic analysis (based on microsatellite loci) to make inferences about functional connectivity between populations of the Prairie Rattlesnake (Crotalus viridis (Rafinesque, 1818)) on oppos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Our results further emphasize an association between high-traffic roads and genetic differentiation in pit vipers (Clark et al, 2010, DiLeo, Row, & Lougheed, 2010, DiLeo et al, 2013, Bushar et al, 2015, Herrmann, Pozarowski, Ochoa, & Schuett, 2017; but see Weyer, Jørgensen, Schmitt, Maxwell, & Anderson, 2014). These findings are in addition to field studies that have suggested the outsized role played by road mortality in snakes, and herpetofauna more generally (Andrews & Gibbons, 2005;Row, Blouin-Demers, & Weatherhead, 2007;Shepard et al, 2008).…”
Section: Copperhead Landscape Genomics and Temporal Considerationssupporting
confidence: 86%
“…Our results further emphasize an association between high-traffic roads and genetic differentiation in pit vipers (Clark et al, 2010, DiLeo, Row, & Lougheed, 2010, DiLeo et al, 2013, Bushar et al, 2015, Herrmann, Pozarowski, Ochoa, & Schuett, 2017; but see Weyer, Jørgensen, Schmitt, Maxwell, & Anderson, 2014). These findings are in addition to field studies that have suggested the outsized role played by road mortality in snakes, and herpetofauna more generally (Andrews & Gibbons, 2005;Row, Blouin-Demers, & Weatherhead, 2007;Shepard et al, 2008).…”
Section: Copperhead Landscape Genomics and Temporal Considerationssupporting
confidence: 86%
“…The early emergence of this pattern may reflect the strong interest of landscape geneticists in movement and dispersal, and a greater tendency for authors to report or comment on species' dispersal behaviour. Some studies have associated large population size, either historical or contemporary, with longer time lags (Ramirez- Barahona & Eguiarte 2014;Weyer et al 2014). For example, large effective population size was associated with an inability to detect genetic effects of a recent road barrier in the prairie rattlesnake (Crotalus viridus), even though an ecological model predicted high road mortality (Weyer et al 2014).…”
Section: Comparison Of Contemporary Genetic Data To Historical Landscmentioning
confidence: 99%
“…Some studies have associated large population size, either historical or contemporary, with longer time lags (Ramirez- Barahona & Eguiarte 2014;Weyer et al 2014). For example, large effective population size was associated with an inability to detect genetic effects of a recent road barrier in the prairie rattlesnake (Crotalus viridus), even though an ecological model predicted high road mortality (Weyer et al 2014). Zellmer & Knowles (2009) explained the lack of a detectable time lag in the wood frog by the occurrence of extinction-colonization dynamics.…”
Section: Comparison Of Contemporary Genetic Data To Historical Landscmentioning
confidence: 99%
“…It was surprising that road mortality was not more prevalent in our study, given that roads are a significant source of snake mortality (Bonnet et al 1999;Row et al 2007;Quintero-Ángel et al 2012;Weyer et al 2014). The low road mortality rates we observed may, at least in part, be explained by the observed differences in migration behaviour in the two study landscapes.…”
Section: R a F T 13mentioning
confidence: 52%
“…This is because, all else being equal, a snake that makes more tortuous movements is less likely to encounter a road than a snake that makes straighter movements. In support of this, Weyer et al (2014) found eight times more prairie rattlesnakes on a road near the hibernacula in the semi-natural landscape than on the road D r a f t 14 near the hibernacula in the human-dominated landscape. Actual road mortality rates relative to other sources of mortality (e.g.…”
Section: R a F T 13mentioning
confidence: 86%